International marketing: An Indian adaptation - Kotabe, Masaaki; Helsen, Kristiaan; Maheshwari, Prateek (New Delhi Wiley India Pvt. Ltd., 2021)
nternational Marketing, 8th Edition combines academic rigor, contemporary relevance, and student-friendly readability to review how marketing managers can succeed in the increasingly competitive international business environment. This in-depth yet accessible textbook helps students understand state-of-the-art global marketing practices and recognize how marketing managers work across business functions to achieve overall corporate goals.